Comprehensive analysis of pain syndrome in patients with rheumatoid arthritis - Grygus , I.M.; Nogas, A.O. (Medicni Perspektivi, 2023)
Rheumatoid arthritis is a chronic systemic disease of connective tissue of immune genesis and unknown etiology. In the developed countries of the world, about 1 in 100 people suffer from rheumatoid arthritis, while in Ukraine the occurrence of the disease is 340 cases per 100,000 adult population. Chronic pain syndrome and limitation of joint functions significantly reduce the life quality of patients. At this stage, along with drug therapy, physical rehabilitation / therapy plays an important role in the restorative treatment of patients with rheumatoid arthritis. The purpose of the study is a comprehensive assessment of the main indicators of pain syndrome and morning stiffness of joints in patients with rheumatoid arthritis. 216 patients with rheumatoid arthritis were examined: 178 (82%) of them were women, 38 (18%) were men. The age of the patients is from 25 to 59 (average age is 46±0,24). The diagnosis was established on the basis of the ACR/EULAR 2010 criteria and in accordance with the Order of the Ministry of Health of Ukraine No. 263 dated November 04, 2014. A comprehensive analysis of the pain syndrome in patients with rheumatoid arthritis was carried out. Pain and severity of morning stiffness in the joints were determined using Huskisson’s visual analog scale (VAS, 100 mm). Statistical analysis was performed on the basis of the statistical analysis Statistica 10 (Serial Number: STA999K347150-W) and MEDCALC®. It was found that pain of low intensity was observed in 62 (28,7%), pain of medium intensity – in 120 (55,6%), and maximum intensity pain was experienced by 34 (15,7%) patients. It was found that in women with rheumatoid arthritis of radiological stage I, the average morning stiffness index according to VAS (100 mm) is 46,1±7,3, in men – 45,3±4,8; in women of radiological stage II, the average indicator is 52,6±7,9, in men – 50,3±6,1; in women of radiological stage III, the average indicator is 66,8±5,9, in men – 63,6±1,7. The analysis of the indicators showed that the severity of morning stiffness is more pronounced in women of all radiological stages than in men. All the above determines an urgent need to develop and implement in practice the concept of physical therapy for patients with rheumatoid arthritis in order to reduce the pain syndrome, severity of rheumatoid arthritis, eliminate morning stiffness, improve the functional condition and restore the motor functions of the joints, improve the health and quality of life of patients.